15x2 - 24x + 9 = 3*(5x2 - 8x + 3) = 3*(5x2 - 5x - 3x + 3)= 3*[5x(x - 1) -3*(x - 1)]
= 3*(5x - 3)*(x - 1) . . . . . (A)
3x - 3 = 3*(x - 1) . . . . . . . (B)
So, (A) and (B) have 3*(x - 1) as common factors and cancelling these gives
(A)/(B) = 5x - 3
One-houndred and thirty five.
2x2=4 1x4=4 3x3=9 1x9=9
-3(x - 3)(x + 1)(x + 1)
48 divided by 6 plus 9 is 17.
48 divided by 6 plus 45 divided by 9 = 8 + 5 = 13
(3x3x3 - 3x3)/(3 - 3x3) = (27-9)/(3-9) = 18/(-6) = -3 if you mean: 3x3x3 - (3x3)/(3 - 3x3) = 27 - 9/(-6) = 28 1/2
y
One-houndred and thirty five.
2x2=4 1x4=4 3x3=9 1x9=9
3(x + 3)(x2 - 3x + 9)
-3(x - 3)(x + 1)(x + 1)
-3x3 - 6x2 + 189x = -3x(x2 + 2x - 63) = -3x(x + 9)(x - 7)
it could be anything. What is a? if it is 3 then you do 4x3=12+3x3=9+3=24 * * * * * It is 8a.
16.6667
3x3
48 divided by 6 plus 9 is 17.
breaking the array 3x9=27 3x3=9 3x3=9 3x3=9 9+9+9=27 one more way of doing it is 3x3=9 and 3x6 =18 , 9+18 =27